Importance of static adjustment of knee angle to determine saddle height in cycling - Priego Quesada, J. I.; Canal Jacques, T.; Bini, R. R.; Carpes, F. P. (Journal of Science and Cycling, 2016)
Knee flexion angle is used to determine saddle height during pedaling. However, it is unclear how knee flexion angle at upright standing posture affects measures and interpretation of knee flexion angle during cycling. The objective of this study was to highlight the importance of adjusting knee angle during pedaling according to the knee angle at upright posture. Seventeen cyclists performed three 10 min cycling trials at different saddle heights to induce knee flexion angles (40º, 30º or 20º when crank was at the 6 o`clock position). Knee flexion angle was determined at the sagittal plane during cycling using a 2D motion analysis system. Alteration of saddle height was performed by subtracting the knee flexion determined during an upright standing posture from the observed knee flexion during cycling. Repeatability of knee angles at upright posture in the three trials was very good (ICC=0.73). A reduction in knee flexion angle of 10.6° (95%CI [8.6, 12.6º]) during cycling was found using the adjustment for upright standing posture (p<0.01; effect size>3.0). As a result, saddle height is affected by adjustments based on knee angle measured in upright standing posture. Determining saddle height without adjusting knee angle for upright standing posture could lead to errors with possible effects on performance and/or injury risk.